Measuring environmental noise from airports, oil and gas operations, and traffic with smartphone applications: laboratory and field trials. (November 2018) - Blair, Benjamin; Brindley, Stephen; Hughes, John; Dinkeloo, Eero; McKenzie, Lisa; Adgate, John
Abstract Environmental noise from sources such as traffic, airports, and oil and gas (O&G) operations is associated with nuisance and health concerns. Smartphones with external microphones have been recommended for environmental noise monitoring and may be useful tools for citizen science, but are not validated against reference methods. We evaluated laboratory performance of three smartphone/application (app) configurations recommended for environmental noise measurement. Two smartphone/app configurations were also compared to a reference sampler, a type 1 sound level meter (SLM) at ten outdoor sites with traffic, airport, and O&G noise. To evaluate performance, we compared the mean squared error, variance, bias, and Krippendorff's Alpha by smartphone/app combination and testing location for both audible (A-weighted) and low-frequency (C-weighted) noise. We observed that laboratory measurements were in strong agreement with a reference sampler. The field A-weighted noise level results had strong agreement with the SLM at several outdoor sites, but our C-weighted noise results ranged from moderate to substantial agreement. For our tested configurations, we find that smartphones with external microphones are reliable proxies for measuring A- and C-weighted noise in a laboratory setting. Outdoor performance depends on noise source type, weighting, and precision and accuracy needs of the investigation.